Education matters: cumulative advantages and disadvantages amongst Portuguese older men - Vilhena, Carla (2020)
Our paper sought to analyse the influence of the educational background over various dimensions of the lives of Portuguese older men (age 60+) across the life course. Drawing on the theory of cumulative advantages and disadvantages we used biographical research, namely narrative interviews with men from different educational background: men with a very low educational background and men with a medium/high educational background. Our results show the influence of educational background in the life course, and how it can contribute to accumulation of advantages/disadvantages that explain their biographies and the very different situations in which they live today.